Recurrent Cometary Activity Discovered on Quasi-Hilda Jupiter Family Comet 362P/(457175) 2008 GO98 - Kennedy A. Farrell; Colin Orion Chandler; Chadwick A. Trujillo; William J. Oldroyd; Jarod A. DeSpain; Mark Jesus Mendoza Magbanua; Maxwell K. Frissell; Phineas Stone (The Astrophysical Journal Letters)
We report the discovery of recurrent activity on quasi-Hilda comet (QHC) 362P/(457175) 2008 GO _98 . The first activity epoch was discovered during the perihelion passage of 362P in 2016, so we were motivated to observe it for recurrent cometary activity near its next perihelion passage (UT 2024 July 20). We obtained observations with the Lowell Discovery Telescope, the Astrophysical Research Consortium telescope, and the Vatican Advanced Technology Telescope and identified a second activity epoch when 362P had a true anomaly ( ν ) as early as 318 $\mathop{.}\limits^{\unicode{x000b0}}$ 1. We conducted archival searches of six repositories and identified images obtained with Canada–France–Hawaii Telescope MegaCam, Dark Energy Camera, Pan-STARRS 1, SkyMapper, Zwicky Transient Facility, and Las Cumbres Observatory Global Telescope network data. Using these data, we identified activity from a previously unreported time span, and we did not detect activity when 362P was away from perihelion, specifically 83 ^∘ < ν < 318 ^∘ . Detection of activity near perihelion and absence of activity away from perihelion suggest thermally driven activity and volatile sublimation. Our dynamical simulations suggest 362P is a QHC, and it will remain in a combined Jupiter-family comet (JFC) and quasi-Hilda orbit over the next 1 kyr though it will become increasingly chaotic nearing the end of this timeframe. Our reverse simulations suggest 362P may have migrated from the orbit of a long-period comet (∼53%) or Centaur (∼32%); otherwise it remained a JFC (∼15%) over the previous 100 kyr. We recommend additional telescope observations from the community as 362P continues outbound from its perihelion on UT 2024 July 20, as well as continued observations for a third activity epoch.